2020
DOI: 10.3389/fpsyt.2020.00723
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Item Responses to the Patient Health Questionnaire-9: Evidence From the National Health and Nutrition Examination Survey

Abstract: Background Epidemiological studies have shown that total scores in depression screening scales change with age, but the mechanism underlying these age-related changes remains unclear. Previous research has indicated that item responses in depression screening scales exhibit characteristic distributions in the general population. We analyzed Patient Health Questionnaire-9 (PHQ-9) data from a representative survey conducted in the USA, to determine how the response pattern for each item changed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For both sexes, the item responses for the GAD-7 and PHQ-8 exhibited the same mathematical pattern. Previous analyses have reported that the item responses for depression rating scales show the same mathematical pattern regardless of age and nationality [13,32]. Taken together, item responses on the GAD-7 and depression rating scales may follow the same characteristic pattern regardless of demographic factors, such as sex, age, and nationality.…”
Section: Discussionmentioning
confidence: 83%
“…For both sexes, the item responses for the GAD-7 and PHQ-8 exhibited the same mathematical pattern. Previous analyses have reported that the item responses for depression rating scales show the same mathematical pattern regardless of age and nationality [13,32]. Taken together, item responses on the GAD-7 and depression rating scales may follow the same characteristic pattern regardless of demographic factors, such as sex, age, and nationality.…”
Section: Discussionmentioning
confidence: 83%
“…Prior research in this area appears inconsistent. Wada et al40 found a similar negative association between age and PHQ-9 score in a sample of 356 patients undergoing cancer treatment, while Tomitaka et al41 found that PHQ-9 score increased to middle age, then decreased from age 60 and over in a sample of 17,000 US adults. It appears that further work is warranted, and we note that our results align with those of Tomitaka with support for a potential nonlinear association between these variables, though we again highlight that neither linear nor quadratic functions were statistically significant.…”
Section: Discussionmentioning
confidence: 83%